Adhesive tape

By using high -content bio -source carbon (methyl) acrylic symbols in the adhesive zone, and optimizing its composition and performance, the problem of brutal bonding bands in high temperature and high humidity environments and large environmental loads have been solved. The effect of high transparency and high adhesion.

CN119365556APending Publication Date: 2025-01-24SEKISUI CHEMICAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380051057.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-27
Filing Date
2023-12-26
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing adhesive tapes are prone to whitening in high temperature and high humidity environments, and have a large environmental load, making it difficult to meet the needs of biologically sourced materials.

Method used

The (methyl -based) acrylic symbol of carbon containing more than 30%of biological sources is used as the main component of the adhesive layer, and by adjusting the composition of the coefficient and cluster by adjusting the water vapor Optical transparency and adhesion.

Benefits of technology

It is realized to maintain optical transparency and high adhesion in high temperature and high humidity environment, while reducing the requirements of environmental load and meet the requirements of biological source materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119365556A_ABST
    Figure CN119365556A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide an adhesive tape which can reduce environmental burden and has excellent optical transparency even when exposed to a high-temperature, high-humidity environment. The present invention relates to an adhesive tape having an adhesive layer, the adhesive layer containing a (meth) acrylic copolymer, the content of biogenic carbon in the adhesive layer being 30% or more, and the adhesive tape satisfying at least one configuration selected from the group consisting of a first configuration and a second configuration. The first configuration is that the water vapor transmission coefficient P of the adhesive layer calculated by the following formula (i) is 11 g * mm / (m < 2 > * day) or more, in the following formula (i), WVTR represents the water vapor transmission rate (g / (m < 2 > * day)) per unit area of the adhesive layer in an environment of 40 DEG C and 90% RH, and t represents the thickness (mm) of the adhesive layer. And a second configuration in which the (meth) acrylic copolymer contains: at least one type of structural unit selected from the group consisting of structural units derived from n-heptyl (meth) acrylate and structural units derived from 2-octyl (meth) acrylate; and a structural unit derived from a nitrogen atom-containing monomer. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to adhesive tapes. Background Art

[0002] Adhesive tapes having an adhesive layer containing an adhesive have been widely used to fix components in electronic components, vehicles, houses, and building materials (for example, Patent Documents 1 to 3). Specifically, adhesive tapes are used, for example, to adhere a cover plate for protecting the surface of a portable electronic device to a touch panel module or a display panel module, or to adhere a touch panel module to a display panel module.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2015-052050

[0006] Patent Document 2: Japanese Patent Application Publication No. 2015-021067

[0007] Patent Document 3: Japanese Patent Application Publication No. 2015-120876 Summary of the invention

[0008] Problems to be solved by the invention

[0009] In recent years, the exhaustion of petroleum resources and the emission of carbon dioxide caused by the combustion of petroleum-derived products have been considered as problems. Therefore, with the medical field and the packaging material field as the center, attempts have been made to save petroleum resources and reduce environmental load by using materials of biological origin to replace materials of petroleum origin. Such attempts have spread to all fields, and the use of materials of biological origin is also required in the field of adhesive tapes. In addition, for the adhesive tapes used in the bonding of electronic components, etc., it is required that metals and metal oxides are not easily corroded. In addition, the adhesive tapes used in the bonding of display panel modules, etc. require high optical transparency, but the previous adhesive tapes sometimes have the problem of whitening under high temperature and high humidity environments.

[0010] An object of the present invention is to provide a pressure-sensitive adhesive tape that can reduce environmental load and has excellent optical transparency even when exposed to a high-temperature and high-humidity environment.

[0011] Means for solving problems

[0012] The present disclosure 1 relates to an adhesive tape, characterized in that it has an adhesive layer, the adhesive layer contains a (meth)acrylic copolymer, the content of bio-derived carbon in the adhesive layer is 30% or more, and the adhesive tape satisfies at least one structure selected from the following first structure and the following second structure.

[0013] First configuration: The water vapor permeability coefficient P of the adhesive layer calculated by the following formula (i) is 11 g·mm / (m 2 ·day) or above;

[0014] Second configuration: The (meth)acrylic acid-based copolymer includes at least one structural unit selected from the group consisting of a structural unit derived from n-heptyl (meth)acrylate and a structural unit derived from 2-octyl (meth)acrylate, and a structural unit derived from a nitrogen atom-containing monomer.

[0015] Present Disclosure 2 relates to the pressure-sensitive adhesive tape of Present Disclosure 1, which satisfies the above-mentioned first configuration.

[0016] The third disclosure relates to the pressure-sensitive adhesive tape of the second disclosure, wherein the (meth)acrylic copolymer includes at least one structural unit selected from the group consisting of a structural unit derived from n-heptyl (meth)acrylate and a structural unit derived from 2-octyl (meth)acrylate.

[0017] Present disclosure 4 relates to the pressure-sensitive adhesive tape of present disclosure 2 or 3, wherein the (meth)acrylic copolymer includes at least one structural unit selected from the group consisting of a structural unit derived from a hydroxyl group-containing monomer and a structural unit derived from a nitrogen atom-containing monomer.

[0018] Present disclosure 5 relates to the pressure-sensitive adhesive tape of present disclosure 1, 2, 3, or 4, which satisfies the above-mentioned second configuration.

[0019] Present disclosure 6 relates to the pressure-sensitive adhesive tape of present disclosure 5, wherein the (meth)acrylic copolymer further includes a structural unit derived from a hydroxyl group-containing monomer.

[0020] Present disclosure 7 relates to the pressure-sensitive adhesive tape of present disclosure 4 or 6, wherein the content ratio of the structural unit derived from the hydroxyl group-containing monomer in the (meth)acrylic copolymer is 5% by mass or more and 30% by mass or less.

[0021] Disclosure 8 relates to the adhesive tape of Disclosure 1, 2, 3, 4, 5, 6 or 7, wherein the (meth)acrylic copolymer includes a structural unit derived from a (meth)acrylic ester containing biogenic carbon.

[0022] The ninth disclosure relates to the pressure-sensitive adhesive tape of the eighth disclosure, wherein at least one structural unit selected from the structural unit derived from n-heptyl (meth)acrylate and the structural unit derived from 2-octyl (meth)acrylate contains biogenic carbon.

[0023] Disclosure 10 relates to the adhesive tape of Disclosure 4, 5, 6, 7, 8 or 9, wherein the structural unit derived from the nitrogen atom-containing monomer includes a structural unit derived from an amide group-containing monomer.

[0024] Present disclosure 11 relates to the pressure-sensitive adhesive tape of present disclosure 4, 5, 6, 7, 8, 9 or 10, wherein the content ratio of the structural unit derived from the nitrogen atom-containing monomer in the (meth)acrylic copolymer is 5% by mass or more and 10% by mass or less.

[0025] Disclosure 12 relates to the pressure-sensitive adhesive tape of Disclosure 4, 5, 6, 7, 8, 9, 10 or 11, wherein the total content ratio of the structural unit derived from the hydroxyl group-containing monomer and the structural unit derived from the nitrogen atom-containing monomer in the (meth)acrylic copolymer is 10% by mass or more and 30% by mass or less.

[0026] Disclosure 13 relates to the pressure-sensitive adhesive tape of Disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12, wherein the (meth)acrylic copolymer contains a structural unit derived from a carboxyl group-containing monomer, and the content ratio of the structural unit derived from the carboxyl group-containing monomer in the (meth)acrylic copolymer is less than 0.5% by mass.

[0027] Present disclosure 14 relates to the pressure-sensitive adhesive tape of Present Disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 or 13, wherein the (meth)acrylic copolymer includes a structural unit derived from isobornyl (meth)acrylate.

[0028] Present disclosure 15 relates to the pressure-sensitive adhesive tape of present disclosure 14, wherein a content ratio of the structural unit derived from isobornyl (meth)acrylate in the (meth)acrylic copolymer is 10% by mass or more and 45% by mass or less.

[0029] Present disclosure 16 relates to the pressure-sensitive adhesive tape of present disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15, wherein the weight average molecular weight (Mw) of the (meth)acrylic copolymer is 300,000 or more and 900,000 or less.

[0030] Present disclosure 17 relates to the pressure-sensitive adhesive tape of present disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 or 16, wherein the pressure-sensitive adhesive layer contains a silane coupling agent.

[0031] Disclosure 18 relates to the pressure-sensitive adhesive tape of Disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16 or 17, wherein the pressure-sensitive adhesive layer has a gel fraction of 40% by mass or more and 95% by mass or less.

[0032] Disclosure 19 relates to the adhesive tape of Disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17 or 18, wherein the shear storage modulus of the adhesive layer at 23° C. is 0.5×10 5 Pa or more and 3.0×10 6 Below Pa.

[0033] Disclosure 20 relates to the adhesive tape of Disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 or 19, wherein the haze value of the adhesive tape at a temperature of not less than 20°C and not more than 25°C is less than 3.0%, and the haze value of the adhesive tape at a temperature of not less than 20°C and not more than 25°C after being allowed to stand for 500 hours in an environment of 65°C and 90% RH is less than 3.0%.

[0034] Disclosure 21 relates to the adhesive tape of Disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20, wherein the adhesive tape has a 180° peel force to glass of 10 N / 25 mm or more at 23°C.

[0035] [Mathematical formula 1]

[0036]

[0037] In formula (i), WVTR represents the water vapor transmission rate per unit area (g / (m 2 ·day)), t represents the thickness (mm) of the above-mentioned adhesive layer.

[0038] Hereinafter, the present invention will be described in detail.

[0039] It should be noted that the adhesive tape satisfying the first configuration described above is also referred to as the "adhesive tape of the first embodiment of the present invention", and the adhesive tape satisfying the second configuration described above is also referred to as the "adhesive tape of the second embodiment of the present invention". In addition, matters common to the adhesive tape of the first embodiment of the present invention and the adhesive tape of the second embodiment of the present invention are not particularly specified, or are described as the "adhesive tape of the present invention".

[0040] The present inventors have studied an adhesive tape containing a (meth)acrylic copolymer in an adhesive layer by adjusting the water vapor permeability coefficient in the adhesive layer to a specific range, making the content of biogenic carbon in the adhesive layer to be a specific ratio or more, and using a specific acrylic monomer and a nitrogen atom-containing monomer as monomers constituting the (meth)acrylic copolymer, and making the content of biogenic carbon in the adhesive layer to be a specific ratio or more. As a result, they found that an adhesive tape having a specific structure can reduce environmental load and has excellent optical transparency even when exposed to a high temperature and high humidity environment, thereby completing the present invention.

[0041] The pressure-sensitive adhesive tape of the present invention has a pressure-sensitive adhesive layer.

[0042] The pressure-sensitive adhesive layer contains a (meth)acrylic copolymer.

[0043] The lower limit of the content of the biogenic carbon in the adhesive layer is 30%. By making the content of the biogenic carbon in the adhesive layer 30% or more, the adhesive tape of the present invention is excellent in terms of saving petroleum resources and reducing the emission of carbon dioxide, and can reduce environmental load. The preferred lower limit of the content of the biogenic carbon in the adhesive layer is 50%, the more preferred lower limit is 55%, and the further preferred lower limit is 60%.

[0044] The upper limit of the content of the biogenic carbon is not particularly limited, and may be 100%.

[0045] It should be noted that biogenic carbon contains a certain proportion of radioactive isotopes (C-14), whereas petroleum-derived carbon contains almost no C-14. Therefore, the biogenic carbon content can be calculated by measuring the concentration of C-14 contained in the adhesive layer. Specifically, it can be measured according to ASTM D6866-22, a standard widely used in the bioplastics industry.

[0046] The content of the biogenic carbon in the adhesive layer can be adjusted by adjusting the content of the (meth)acrylic copolymer containing biogenic carbon and other components containing biogenic carbon in the adhesive layer.

[0047] The pressure-sensitive adhesive tape of the present invention satisfies at least one configuration selected from the following first configuration and the following second configuration.

[0048] First configuration: The water vapor permeability coefficient P of the adhesive layer calculated by the above formula (i) is 11 g·mm / (m 2 ·day) or above;

[0049] Second configuration: The (meth)acrylic acid-based copolymer includes at least one structural unit selected from the group consisting of a structural unit derived from n-heptyl (meth)acrylate and a structural unit derived from 2-octyl (meth)acrylate, and a structural unit derived from a nitrogen atom-containing monomer.

[0050] The pressure-sensitive adhesive tape of the present invention satisfies at least one configuration selected from the following first configuration and the following second configuration. Thus, the pressure-sensitive adhesive tape of the present invention can reduce environmental load and has excellent optical transparency even when exposed to a high-temperature and high-humidity environment.

[0051] The lower limit of the water vapor permeability coefficient P of the pressure-sensitive adhesive layer in the pressure-sensitive adhesive tape of the present invention 1 calculated by the above formula (i) is 11 g·mm / (m 2 ·day). By setting the water vapor permeability coefficient P of the adhesive layer in the adhesive tape of the present invention 1 to 11 g·mm / (m 2 ·day) or more, so that the obtained adhesive tape can suppress whitening and has excellent optical transparency even when exposed to a high temperature and high humidity environment. The preferred lower limit of the water vapor permeability coefficient P of the above-mentioned adhesive layer in the adhesive tape of the present invention 1 is 13g·mm / (m 2 ·day), the more preferred lower limit is 15g·mm / (m 2 ·day).

[0052] In the pressure-sensitive adhesive tape of the second aspect of the present invention, the lower limit of the water vapor permeability coefficient P of the pressure-sensitive adhesive layer calculated by the above formula (i) is preferably 11 g·mm / (m 2 ·day). By setting the water vapor permeability coefficient P of the adhesive layer in the adhesive tape of the second embodiment to 11 g·mm / (m 2 ·day) or more, so that the obtained adhesive tape can further suppress whitening and has excellent optical transparency even when exposed to a high temperature and high humidity environment. The more preferred lower limit of the water vapor permeability coefficient P of the above-mentioned adhesive layer in the adhesive tape of the present invention 2 is 13g·mm / (m 2 ·day), and the further preferred lower limit is 15g·mm / (m 2 ·day).

[0053] From the viewpoint of preventing the display panel module and other components fixed by the adhesive tape from being deteriorated by water vapor, the upper limit of the water vapor transmission coefficient P of the adhesive layer is preferably 30 g·mm / (m 2 ·day), the more preferred upper limit is 25g·mm / (m 2 ·day), and the upper limit is preferably 20g·mm / (m 2 ·day).

[0054] It should be noted that the water vapor permeability coefficient P of the adhesive layer can be obtained as follows: after measuring the water vapor permeability WVTR per unit area of ​​the adhesive layer at 40°C and 90% RH for one day (hereinafter, sometimes referred to as "the water vapor permeability WVTR of the adhesive layer at 40°C and 90% RH"), the water vapor permeability WVTR obtained is used for calculation and the thickness of the adhesive layer. As a method for measuring the water vapor permeability WVTR of the adhesive layer at 40°C and 90% RH, it can be measured by a water vapor permeability humidity test based on the MOCON method under the conditions of 40°C and 90% RH in accordance with JIS K 7129B.

[0055] Generally, the water vapor transmission rate WVTR is inversely proportional to the thickness of the object to be measured. Therefore, the water vapor transmission rate WVTR of the pressure-sensitive adhesive layer at 40° C. and 90% RH is inversely proportional to the thickness of the pressure-sensitive adhesive layer.

[0056] Therefore, by using the water vapor permeability coefficient P of the adhesive layer obtained by multiplying the water vapor permeability WVTR of the adhesive layer at 40° C. and 90% RH by the thickness of the adhesive layer, the water vapor permeability of the adhesive layer can be calculated as a value independent of the thickness of the adhesive layer.

[0057] As a method for adjusting the water vapor permeability coefficient P of the pressure-sensitive adhesive layer and the water vapor permeability WVTR of the pressure-sensitive adhesive layer at 40° C. and 90% RH, for example, a method of adjusting the composition of the (meth)acrylic copolymer described below or the type of the additive described below is preferred.

[0058] The preferred lower limit of the thickness of the adhesive layer is 5 μm, and the preferred upper limit is 500 μm. By making the thickness of the adhesive layer 5 μm or more, the obtained adhesive tape has a higher adhesive force. By making the thickness of the adhesive layer 500 μm or less, the adhesive tape of the present invention can be more suitable for fixing electronic components. The more preferred lower limit of the thickness of the adhesive layer is 10 μm, the further preferred lower limit is 25 μm, the more preferred upper limit is 300 μm, and the further preferred upper limit is 250 μm.

[0059] In the pressure-sensitive adhesive tape of the second aspect of the present invention, the (meth)acrylic acid-based copolymer includes at least one structural unit selected from the group consisting of a structural unit derived from n-heptyl (meth)acrylate and a structural unit derived from 2-octyl (meth)acrylate. The pressure-sensitive adhesive tape obtained by including at least one structural unit selected from the group consisting of a structural unit derived from n-heptyl (meth)acrylate and a structural unit derived from 2-octyl (meth)acrylate in the (meth)acrylic acid-based copolymer has high adhesive strength.

[0060] In the pressure-sensitive adhesive tape of the present invention 1, the (meth)acrylic acid-based copolymer preferably includes at least one selected from the group consisting of a structural unit derived from n-heptyl (meth)acrylate and a structural unit derived from 2-octyl (meth)acrylate. When the (meth)acrylic acid-based copolymer includes at least one selected from the group consisting of a structural unit derived from n-heptyl (meth)acrylate and a structural unit derived from 2-octyl (meth)acrylate, the pressure-sensitive adhesive tape obtained has higher pressure-sensitive adhesive force.

[0061] In addition, in this specification, "(meth)acrylic acid" means acrylic acid or methacrylic acid, and "(meth)acrylate" means acrylate or methacrylate.

[0062] The (meth)acrylic acid-based copolymer preferably includes a structural unit derived from a (meth)acrylic acid ester containing carbon of biological origin. By making the (meth)acrylic acid-based copolymer include a structural unit derived from a (meth)acrylic acid ester containing carbon of biological origin, the content of carbon of biological origin in the adhesive layer is increased, and the environmental load caused by the obtained adhesive tape can be further reduced.

[0063] In addition, in this specification, "comprising carbon of biological origin" means that the biobased carbon content of the compound measured by ASTM D6866-22 is 1% or more.

[0064] At least one structural unit selected from the structural unit derived from n-heptyl (meth)acrylate and the structural unit derived from 2-octyl (meth)acrylate preferably contains carbon derived from biomass. By making at least one structural unit selected from the structural unit derived from n-heptyl (meth)acrylate and the structural unit derived from 2-octyl (meth)acrylate contain carbon derived from biomass, the content of carbon derived from biomass in the adhesive layer is increased, and the environmental load caused by the obtained adhesive tape can be further reduced.

[0065] That is, by making the (meth)acrylic acid-based copolymer include at least one structural unit selected from the group consisting of a structural unit derived from n-heptyl (meth)acrylate containing biogenic carbon and a structural unit derived from 2-octyl (meth)acrylate containing biogenic carbon, the obtained pressure-sensitive adhesive tape can further reduce the environmental load and have higher adhesive strength.

[0066] The above-mentioned n-heptyl (meth)acrylate containing biogenic carbon and the above-mentioned 2-octyl (meth)acrylate containing biogenic carbon are not particularly limited as long as they contain biogenic carbon, and are preferably synthesized by esterification of n-heptyl alcohol as a biogenic material, 2-octanol as a biogenic material, and (meth)acrylic acid. In addition, it is also preferably synthesized by transesterification of n-heptyl alcohol as a biogenic material, 2-octanol as a biogenic material, and (meth)acrylic acid ester.

[0067] The above-mentioned n-heptanol as a bio-derived material can be obtained easily and cheaply by, for example, using a material collected from animals and plants (for example, ricinoleic acid derived from castor oil) as a raw material and then cracking it.

[0068] The above-mentioned 2-octanol as a bio-derived material can be obtained easily and cheaply by using a material collected from animals and plants (for example, ricinoleic acid derived from castor oil) as a raw material and subjecting it to alkali melting.

[0069] The preferred lower limit of the total content ratio of the structural unit derived from n-heptyl (meth)acrylate and the structural unit derived from 2-octyl (meth)acrylate in the (meth)acrylic copolymer is 25% by mass. By setting the total content ratio of the structural unit derived from n-heptyl (meth)acrylate and the structural unit derived from 2-octyl (meth)acrylate to 25% by mass or more, the obtained adhesive tape has a higher adhesive force. In addition, if the total content ratio of the structural unit derived from n-heptyl (meth)acrylate containing carbon from biological sources and the structural unit derived from 2-octyl (meth)acrylate containing carbon from biological sources is 25% by mass or more, the content rate of carbon from biological sources in the adhesive layer can be further increased. The more preferred lower limit of the total content ratio of the structural unit derived from n-heptyl (meth)acrylate and the 2-octyl (meth)acrylate is 35% by mass, the further preferred lower limit is 45% by mass, and the further preferred lower limit is 55% by mass.

[0070] Furthermore, from the viewpoint of adjusting the haze value at room temperature (20° C. to 25° C.) after the pressure-sensitive adhesive tape of the present invention described below is left to stand for 500 hours under an environment of 65° C. and 90% RH, the upper limit of the total content of the structural unit derived from n-heptyl (meth)acrylate and the structural unit derived from 2-octyl (meth)acrylate is preferably 90% by mass, more preferably 85% by mass, and still more preferably 80% by mass.

[0071] In addition, when the (meth)acrylic acid-based copolymer does not contain the structural unit derived from n-heptyl (meth)acrylate or the structural unit derived from 2-octyl (meth)acrylate, the content ratio of the structural unit derived from n-heptyl (meth)acrylate or the structural unit derived from 2-octyl (meth)acrylate contained in the acrylic acid-based copolymer alone is taken as the total content ratio of the structural unit derived from n-heptyl (meth)acrylate and the structural unit derived from 2-octyl (meth)acrylate.

[0072] In addition, the content ratio of the structural unit derived from n-heptyl (meth)acrylate and the structural unit derived from 2-octyl (meth)acrylate in the (meth)acrylic acid-based copolymer can be determined by mass spectrometry analysis of the (meth)acrylic acid-based copolymer and 1 The H-NMR measurement was calculated from the integrated intensity ratio of the peak derived from hydrogen of n-heptyl (meth)acrylate or 2-octyl (meth)acrylate.

[0073] The (meth)acrylic acid-based copolymer preferably includes a structural unit derived from isobornyl (meth)acrylate. When the (meth)acrylic acid-based copolymer includes a structural unit derived from isobornyl (meth)acrylate, the cohesive force of the pressure-sensitive adhesive layer becomes greater, and the pressure-sensitive adhesive tape obtained has a higher pressure-sensitive adhesive force.

[0074] The isobornyl (meth)acrylate preferably contains biogenic carbon. When the isobornyl (meth)acrylate contains biogenic carbon, the biogenic carbon content in the adhesive layer is further increased, and the environmental load caused by the obtained adhesive tape can be further reduced.

[0075] The isobornyl (meth)acrylate containing biogenic carbon is not particularly limited as long as it contains biogenic carbon, but is preferably synthesized by reacting camphene, which is a biogenic material, with (meth)acrylic acid.

[0076] Camphene, which is the bio-derived material, can be obtained easily and cheaply by, for example, isomerizing pinene collected from rosin.

[0077] When the (meth)acrylic acid copolymer contains the structural unit derived from isobornyl (meth)acrylate, the preferred lower limit of the content of the structural unit derived from isobornyl (meth)acrylate in the (meth)acrylic acid copolymer is 3% by mass, and the preferred upper limit is 45% by mass. By making the content of the structural unit derived from isobornyl (meth)acrylate 3% or more, the cohesive force of the adhesive layer becomes greater, and the obtained adhesive tape has a higher adhesive force. By making the content of the structural unit derived from isobornyl (meth)acrylate 45% or less, the adhesive layer does not become too hard, and the obtained adhesive tape has a higher adhesive force. The more preferred lower limit of the content of the structural unit derived from isobornyl (meth)acrylate is 5% by mass, the further preferred lower limit is 10% by mass, the further preferred lower limit is 15% by mass, and the particularly preferred lower limit is 18% by mass, the more preferred upper limit is 40% by mass, the further preferred upper limit is 30% by mass, the further preferred upper limit is 25% by mass, and the particularly preferred upper limit is 22% by mass.

[0078] The content ratio of the structural unit derived from isobornyl (meth)acrylate in the (meth)acrylic acid-based copolymer can be determined by mass spectrometry analysis of the (meth)acrylic acid-based copolymer and 1 The H-NMR measurement was calculated from the integrated intensity ratio of the peak derived from hydrogen of isobornyl (meth)acrylate.

[0079] The (meth)acrylic acid-based copolymer in the adhesive tape of the present invention 1 preferably further comprises at least one structural unit selected from the group consisting of structural units derived from hydroxyl-containing monomers and structural units derived from nitrogen-containing monomers. By making the (meth)acrylic acid-based copolymer comprise at least one structural unit selected from the group consisting of structural units derived from hydroxyl-containing monomers and structural units derived from nitrogen-containing monomers, the polarity of the adhesive layer becomes larger, and it is easy to adjust the water vapor permeability coefficient P of the adhesive layer to the above range. As a result, even when the obtained adhesive tape is exposed to a high temperature and high humidity environment, whitening can be further suppressed, and thus the optical transparency becomes more excellent.

[0080] In addition, by making the (meth)acrylic acid copolymer contain a structural unit derived from a hydroxyl-containing monomer, when the adhesive layer contains a crosslinking agent described later, crosslinking is more easily performed, the durability of the adhesive layer against the displacement and deformation of the adherend in a high temperature and high humidity environment becomes higher, and the adhesion of the obtained adhesive tape to the adherend is further improved. By making the (meth)acrylic acid copolymer contain a structural unit derived from a nitrogen atom-containing monomer, the cohesive force of the adhesive layer becomes larger, and the obtained adhesive tape has a higher adhesive force.

[0081] The structural unit derived from the hydroxyl group-containing monomer and the structural unit derived from the nitrogen atom-containing monomer may be used alone or in combination of two or more.

[0082] The (meth)acrylic acid-based copolymer in the adhesive tape of the second aspect of the present invention contains a structural unit derived from a nitrogen-containing monomer. By making the (meth)acrylic acid-based copolymer contain a structural unit derived from a nitrogen-containing monomer, the polarity of the adhesive layer becomes larger, and even when the obtained adhesive tape is exposed to a high-temperature and high-humidity environment, whitening can be suppressed, so that the optical transparency is excellent. In addition, the cohesive force of the adhesive layer becomes larger, and the obtained adhesive tape has high adhesive force.

[0083] The (meth) acrylic copolymer in the adhesive tape of the second aspect of the present invention preferably further comprises a structural unit derived from a hydroxyl-containing monomer. By making the (meth) acrylic copolymer further comprise a structural unit derived from a hydroxyl-containing monomer, the polarity of the adhesive layer becomes larger, and even when the obtained adhesive tape is exposed to a high temperature and high humidity environment, whitening can be further suppressed, so that the optical transparency becomes more excellent. In addition, when the adhesive layer contains a crosslinking agent described later, crosslinking is more likely to proceed, the durability of the adhesive layer against the deviation and deformation of the adherend in a high temperature and high humidity environment becomes higher, and the adhesion of the obtained adhesive tape to the adherend is further improved.

[0084] Examples of the hydroxyl group-containing monomer include 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 1-methyl-3-hydroxypropyl (meth)acrylate, 1-methyl-2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 1-methyl-2-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 1-ethyl-2-hydroxyethyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, 7-hydroxyheptyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, and 9-hydroxynonyl (meth)acrylate. Among them, the hydroxyl-containing monomer preferably includes at least one selected from 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 1-methyl-3-hydroxypropyl (meth)acrylate, 1-methyl-2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate. 2-hydroxypropyl (meth)acrylate is more preferred from the viewpoint of good reactivity balance in structure and easy control of reactivity with a cross-linking agent.

[0085] The hydroxyl group-containing monomer preferably contains biogenic carbon. When the hydroxyl group-containing monomer contains biogenic carbon, the biogenic carbon content in the pressure-sensitive adhesive layer is further increased, and the environmental load of the obtained pressure-sensitive adhesive tape can be further reduced.

[0086] The preferred lower limit of the content ratio of the structural unit from the hydroxyl-containing monomer in the (meth) acrylic copolymer is 5% by mass, and the preferred upper limit is 30% by mass. By making the content ratio of the structural unit from the hydroxyl-containing monomer more than 5% by mass, the polarity of the adhesive layer becomes larger, and it is easy to adjust the water vapor permeability coefficient P of the adhesive layer to the above range. As a result, even if the obtained adhesive tape is exposed to a high temperature and high humidity environment, whitening can be further suppressed, so the optical transparency becomes more excellent. By making the content ratio of the structural unit from the hydroxyl-containing monomer less than 30% by mass, the adhesive layer will not become too hard, and the obtained adhesive tape has a higher adhesive force. The more preferred lower limit of the content ratio of the structural unit from the hydroxyl-containing monomer is 6% by mass, the further preferred lower limit is 7% by mass, the more preferred upper limit is 25% by mass, the further preferred upper limit is 20% by mass, and the further preferred upper limit is 15% by mass.

[0087] The content ratio of the structural unit derived from the hydroxyl-containing monomer in the (meth)acrylic copolymer can be determined by mass spectrometry analysis of the (meth)acrylic copolymer and 1 The H-NMR measurement was calculated from the integrated intensity ratio of the peak derived from hydrogen of the hydroxyl group-containing monomer.

[0088] Examples of the nitrogen atom-containing monomer include amide group-containing monomers, nitrile group-containing monomers, amino group-containing monomers, isocyanate group-containing monomers, etc. Among them, amide group-containing monomers are preferred because they have a high glass transition temperature, the cohesive force of the adhesive layer is increased, and the resulting adhesive tape has higher adhesive force.

[0089] Examples of the amide group-containing monomer include acrylic monomers having an amide group, such as (meth)acrylamide, dimethyl (meth)acrylamide, diethyl (meth)acrylamide, isopropyl (meth)acrylamide, tert-butyl (meth)acrylamide, methoxymethyl (meth)acrylamide, and butoxymethyl (meth)acrylamide. Among them, (meth)acrylamide, dimethyl (meth)acrylamide, and diethyl (meth)acrylamide are preferred in terms of easy availability and easy handling.

[0090] Examples of the nitrile group-containing monomer include acrylic monomers having a nitrile group such as (meth)acrylonitrile.

[0091] The nitrogen atom-containing monomer preferably contains biogenic carbon. When the nitrogen atom-containing monomer contains biogenic carbon, the biogenic carbon content in the pressure-sensitive adhesive layer is further increased, and the environmental load of the resulting pressure-sensitive adhesive tape can be further reduced.

[0092] The preferred lower limit of the content ratio of the structural unit derived from the nitrogen-containing monomer in the (meth) acrylic copolymer is 5% by mass, and the preferred upper limit is 25% by mass. By making the content ratio of the structural unit derived from the nitrogen-containing monomer more than 5% by mass, the polarity of the adhesive layer becomes larger, and it is easy to adjust the water vapor permeability coefficient P of the adhesive layer to the above range. As a result, even when the obtained adhesive tape is exposed to a high temperature and high humidity environment, whitening can be further suppressed, so the optical transparency becomes more excellent. In addition, the cohesive force of the adhesive layer becomes larger, and the obtained adhesive tape has a higher adhesive force. By making the content ratio of the structural unit derived from the nitrogen-containing monomer less than 25% by mass, the adhesive layer will not become too hard, and the obtained adhesive tape has a higher adhesive force. The more preferred lower limit of the content ratio of the structural units derived from the nitrogen atom-containing monomer is 5.5% by mass, the further preferred lower limit is 6% by mass, the further preferred lower limit is 7% by mass, the more preferred upper limit is 20% by mass, the further preferred upper limit is 15% by mass, the further preferred upper limit is 10% by mass, the particularly preferred upper limit is 9.5% by mass, and the particularly preferred upper limit is 9% by mass.

[0093] The content ratio of the structural unit derived from the nitrogen atom-containing monomer in the (meth)acrylic copolymer can be determined by mass spectrometry analysis of the (meth)acrylic copolymer and 1 The H-NMR measurement was calculated from the integrated intensity ratio of the peak derived from hydrogen of the above-mentioned nitrogen atom-containing monomer.

[0094] The preferred lower limit of the total content ratio of the structural unit derived from the hydroxyl-containing monomer and the structural unit derived from the nitrogen-containing monomer in the (meth) acrylic copolymer is 10% by mass, and the preferred upper limit is 30% by mass. By making the total content ratio of the structural unit derived from the hydroxyl-containing monomer and the structural unit derived from the nitrogen-containing monomer 10% or more by mass, the polarity of the adhesive layer becomes larger, and it is easy to adjust the water vapor permeability coefficient P of the adhesive layer to the above range. As a result, even if the obtained adhesive tape is exposed to a high temperature and high humidity environment, whitening can be further suppressed, so the optical transparency becomes better. By making the total content ratio of the structural unit derived from the hydroxyl-containing monomer and the structural unit derived from the nitrogen-containing monomer 30% or less by mass, the adhesive layer will not become too hard, and the obtained adhesive tape has a higher adhesive force. The more preferred lower limit of the total content ratio of the structural unit derived from the hydroxyl-containing monomer and the structural unit derived from the nitrogen-containing monomer is 12% by mass, the further preferred lower limit is 14% by mass, the more preferred upper limit is 28% by mass, and the further preferred upper limit is 26% by mass.

[0095] It should be noted that, when the above-mentioned (meth)acrylic copolymer does not contain the above-mentioned structural unit derived from the hydroxyl group-containing monomer or the above-mentioned structural unit derived from the nitrogen atom-containing monomer, the content ratio of the structural unit derived from the hydroxyl group-containing monomer or the above-mentioned structural unit derived from the nitrogen atom-containing monomer contained in the above-mentioned acrylic copolymer alone is taken as the total content ratio of the structural unit derived from the hydroxyl group-containing monomer and the structural unit derived from the nitrogen atom-containing monomer.

[0096] The (meth)acrylic copolymer may further include a structural unit derived from a monomer containing a polar functional group other than the nitrogen atom-containing monomer and the hydroxyl group-containing monomer. By including the structural unit derived from the monomer containing a polar functional group, the polarity of the adhesive layer becomes larger, and even when the obtained adhesive tape is exposed to a high temperature and high humidity environment, whitening can be further suppressed, thereby achieving better optical transparency.

[0097] As the structural units derived from other monomers containing polar functional groups, for example, there can be mentioned: structural units derived from carboxyl-containing monomers, structural units derived from glycidyl-containing monomers, etc. These structural units derived from other monomers containing polar functional groups can be used alone or in combination of two or more. Among them, from the viewpoint that the cohesive force of the above-mentioned adhesive layer becomes greater and the obtained adhesive tape has higher adhesive force, structural units derived from carboxyl-containing monomers are preferred.

[0098] Examples of the carboxyl group-containing monomer include acrylic monomers having a carboxyl group such as (meth)acrylic acid.

[0099] The carboxyl group-containing monomer preferably contains biogenic carbon. When the carboxyl group-containing monomer contains biogenic carbon, the biogenic carbon content in the pressure-sensitive adhesive layer increases, and the environmental load caused by the obtained pressure-sensitive adhesive tape can be further reduced.

[0100] Generally, in electronic components and vehicle-mounted components as adherends of adhesive tapes, metals and metal oxides are used in touch sensors, copper wiring, etc. When an adhesive tape containing a (meth)acrylic acid copolymer copolymerized with a large amount of the above-mentioned carboxyl group-containing monomer is used around such metals and metal oxides, there is a problem that the metals and metal oxides corrode and cause defects over time.

[0101] Therefore, the content of the structural unit derived from the carboxyl group-containing monomer in the (meth)acrylic copolymer is preferably less than 0.5% by mass. By making the content of the structural unit derived from the carboxyl group-containing monomer less than 0.5% by mass, the corrosiveness of the obtained adhesive tape to metals and metal oxides (metal corrosion of the adhesive tape) can be further suppressed.

[0102] Furthermore, from the viewpoint of metal corrosivity, it is more preferred that the (meth)acrylic copolymer does not contain the structural unit derived from the carboxyl group-containing monomer.

[0103] The content ratio of the structural unit derived from the carboxyl group-containing monomer in the (meth)acrylic acid-based copolymer can be determined by mass spectrometry analysis of the (meth)acrylic acid-based copolymer and 1 The H-NMR measurement was calculated from the integrated intensity ratio of the peak derived from hydrogen of the carboxyl group-containing monomer.

[0104] The (meth)acrylic copolymer may contain a glycidyl group-containing monomer.

[0105] Examples of the glycidyl group-containing monomer include acrylic monomers having a glycidyl group such as glycidyl (meth)acrylate.

[0106] The (meth)acrylic copolymer may have structural units derived from other monomers in addition to the structural units derived from n-heptyl (meth)acrylate, the structural units derived from 2-octyl (meth)acrylate, the structural units derived from isobornyl (meth)acrylate, the structural units derived from the hydroxyl group-containing monomer, the structural units derived from the nitrogen atom-containing monomer, the structural units derived from the carboxyl group-containing monomer, and the structural units derived from the glycidyl group-containing monomer.

[0107] Examples of the other monomers include alkyl (meth)acrylates other than the above-mentioned n-heptyl (meth)acrylate and the above-mentioned 2-octyl (meth)acrylate.

[0108] Examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, myristyl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, esters of 5,7,7-trimethyl-2-(1,3,3-trimethylbutyl)-1-octanol and (meth)acrylic acid, esters of alcohols having a total carbon number of 18 and having one or two methyl groups in a linear main chain and (meth)acrylic acid, behenyl (meth)acrylate, and eicosyl (meth)acrylate. These alkyl (meth)acrylates may be used alone or in combination of two or more.

[0109] In addition, examples of the other monomers include cyclohexyl (meth)acrylate, benzyl (meth)acrylate, 2-butoxyethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, polypropylene glycol mono(meth)acrylate, etc. In addition, various monomers used in common acrylic polymers such as vinyl carboxylate such as vinyl acetate and styrene can also be used as the other monomers. These other monomers can be used alone or in combination of two or more.

[0110] The content ratio of the structural units derived from other monomers in the (meth)acrylic acid-based copolymer can be determined by mass spectrometry analysis of the (meth)acrylic acid-based copolymer and 1 The H-NMR measurement was performed and calculated from the integrated intensity ratio of the peak derived from hydrogen of each monomer.

[0111] The above-mentioned polar functional group-containing monomer and the above-mentioned other monomers preferably contain carbon of biological origin, but may not contain carbon of biological origin and may be composed only of materials of petroleum origin. Theoretically, all monomers constituting the above-mentioned (meth)acrylic acid copolymer may be monomers containing carbon of biological origin. From the viewpoint of the cost and productivity of the adhesive tape, monomers containing carbon of biological origin which are relatively inexpensive and easily available may be used, and monomers composed only of materials of petroleum origin may be combined therewith.

[0112] The preferred lower limit of the weight average molecular weight (Mw) of the (meth) acrylic copolymer is 300,000, and the preferred upper limit is 900,000. By making the weight average molecular weight of the (meth) acrylic copolymer more than 300,000, the cohesive force of the adhesive layer becomes greater, and the obtained adhesive tape has a higher adhesive force. By making the weight average molecular weight of the (meth) acrylic copolymer less than 900,000, the adhesive layer does not become too hard, and the obtained adhesive tape has a higher adhesive force. In addition, the viscosity of the solution containing the (meth) acrylic copolymer described later is not easy to become too large, so the smoothness of the obtained adhesive tape is further improved, and thus the lamination property becomes more excellent. The more preferred lower limit of the weight average molecular weight of the (meth) acrylic copolymer is 400,000, and the further preferred lower limit is 450,000, and the more preferred upper limit is 850,000, and the further preferred upper limit is 800,000.

[0113] It should be noted that in this specification, the weight average molecular weight (Mw) is a weight average molecular weight based on standard polystyrene conversion measured by GPC (Gel Permeation Chromatography). Specifically, the (meth)acrylic copolymer is diluted 50 times with tetrahydrofuran (THF), and the obtained dilution is filtered with a filter (material: polytetrafluoroethylene, pore size: 0.2μm) to prepare a measurement sample. Next, the measurement sample is supplied to a gel permeation chromatograph (for example, "2690 Separations Module" manufactured by Waters Company), and GPC measurement is performed under the conditions of a sample flow rate of 1mL / min and a column temperature of 40°C. The polystyrene conversion molecular weight of the (meth)acrylic copolymer is measured, and this value is used as the weight average molecular weight of the (meth)acrylic copolymer.

[0114] The upper limit of the glass transition temperature (Tg) of the (meth)acrylic copolymer is preferably -20°C. When the glass transition temperature (Tg) of the (meth)acrylic copolymer is -20°C or less, the cohesive force of the adhesive layer becomes greater, and the followability of the obtained adhesive tape to the adherend is improved, and the adhesive force becomes higher. The upper limit of the glass transition temperature (Tg) of the (meth)acrylic copolymer is more preferably -25°C, and the upper limit is still more preferably -30°C.

[0115] The lower limit of the glass transition temperature (Tg) of the (meth)acrylic copolymer is not particularly limited, but is usually -90°C or higher, and preferably -80°C or higher.

[0116] The glass transition temperature (Tg) of the (meth)acrylic copolymer can be determined by, for example, differential scanning calorimetry.

[0117] The preferred upper limit of the acid value of the (meth)acrylic acid copolymer is 5 mgKOH / g. By setting the acid value of the (meth)acrylic acid copolymer to 5 mgKOH / g or less, the metal corrosiveness of the obtained adhesive tape can be further suppressed. The more preferred upper limit of the acid value of the (meth)acrylic acid copolymer is 1 mgKOH / g.

[0118] The lower limit of the acid value of the (meth)acrylic acid-based copolymer is not particularly limited, and may be 0 mgKOH / g.

[0119] In this specification, the acid value refers to the number of mg of potassium hydroxide required to neutralize the acid contained in 1 g of a sample, and the acid value of the (meth)acrylic acid-based copolymer can be determined by, for example, a potentiometric titration method in accordance with JIS K 0070.

[0120] The (meth)acrylic acid-based copolymer can be obtained by polymerizing a monomer mixture serving as a raw material by subjecting it to a radical reaction in the presence of a polymerization initiator.

[0121] As the above-mentioned free radical reaction mode, for example, living radical polymerization, free radical polymerization, etc. According to living radical polymerization, compared with free radical polymerization, a copolymer having a more uniform molecular weight and composition can be obtained, and the generation of low molecular weight components can be suppressed, so that the cohesive force of the obtained adhesive layer becomes larger, and the adhesive force of the obtained adhesive tape has a higher adhesive force.

[0122] As a method for polymerizing the monomer mixture, conventionally known methods can be used, for example, solution polymerization (boiling point polymerization or constant temperature polymerization), UV polymerization, emulsion polymerization, suspension polymerization, bulk polymerization, etc. Among them, solution polymerization and UV polymerization are preferred from the perspective of increasing the adhesive strength of the resulting adhesive tape.

[0123] When solution polymerization is used as a method for polymerizing the above-mentioned monomer mixture, a solution containing the above-mentioned (meth)acrylic acid copolymer can be obtained. As a reaction solvent used in solution polymerization, as a reaction solvent, ethyl acetate, toluene, methyl ethyl ketone, dimethyl sulfoxide, ethanol, acetone, diethyl ether, etc. can be mentioned. These reaction solvents can be used alone or in combination of two or more.

[0124] Examples of the polymerization initiator include organic peroxides and azo compounds, etc. Among them, organic peroxides are preferred because the reaction temperature can be controlled and the molecular weight of the obtained (meth)acrylic polymer can be easily adjusted.

[0125] Examples of the organic peroxide include 1,1-bis(tert-hexylperoxy)-3,3,5-trimethylcyclohexane, tert-hexyl peroxypivalate, tert-butyl peroxypivalate, 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy)hexane, tert-hexyl peroxy-2-ethylhexanoate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxyisobutyrate, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxylaurate, diisobutyryl peroxide, cumyl peroxyneodecanoate, di-n-propyl peroxydicarbonate, diisopropyl peroxydicarbonate, di-sec-butyl peroxydicarbonate, 1,1,3,3-tetramethylbutyl peroxyneodecanoate, Peroxydicarbonate, di(4-tert-butylcyclohexyl) ester, di(2-ethylhexyl) peroxydicarbonate, tert-hexyl peroxyneodecanoate, tert-butyl peroxyneodecanoate, tert-butyl peroxyneoheptanoate, di(3,5,5-trimethylhexanoyl) peroxide, dilauroyl peroxide, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, disuccinic acid peroxide, di(4-methylbenzoyl) peroxide, di(3-methylbenzoyl) peroxide, benzoyl (3-methylbenzoyl) peroxide, dibenzoyl peroxide, Dibenzoyl peroxide (Japanese: peroxydibenziru), 1,1-di(tert-butylperoxy)-2-methylhexane (Japanese: 1,1-di(t-butylperoxy)-2-methylhexane), 1,1-di(tert-hexylperoxy)cyclohexane, 1,1-di(tert-butylperoxy)cyclohexane, 2,2-bis(4,4-di(tert-butylperoxy)cyclohexyl)propane, tert-hexylperoxyisopropylmonocarbonate, tert-butylperoxymaleate, tert-butylperoxyisopropylmonocarbonate, tert-butylperoxy2-octylhexylmonocarbonate, tert-hexylperoxybenzoate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, Butyl peroxyacetate, 2,2-di(tert-butylperoxy)butane, tert-butyl peroxybenzoate, n-butyl-4,4-di(tert-butylperoxy)valerate, di(2-tert-butylperoxyisopropyl)benzene, dicumyl peroxide, di-tert-hexyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, tert-butylcumyl peroxide, di-tert-butyl peroxide, p-menthane hydroperoxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne-3, diisopropylbenzene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, isopropylbenzene hydroperoxide, tert-butyl hydroperoxide, 2,3-dimethyl-2,3-diphenylbutane, etc.

[0126] Examples of the azo compound include azobisisobutyronitrile and azobiscyclohexanecarbonitrile.

[0127] These polymerization initiators may be used alone or in combination of two or more.

[0128] In addition, when the free radical reaction is the living radical polymerization, the polymerization initiator may be, for example, an organic tellurium polymerization initiator. The organic tellurium polymerization initiator is not particularly limited as long as it is an organic tellurium polymerization initiator commonly used in living radical polymerization, and may be, for example, an organic tellurium compound, an organic telluride compound, etc. It should be noted that in the living radical polymerization, in addition to the organic tellurium polymerization initiator, the azo compound may be used as the polymerization initiator for the purpose of accelerating the polymerization rate.

[0129] The preferred lower limit of the solid content concentration of the solution containing the (meth) acrylic copolymer is 10% by mass, and the preferred upper limit is 80% by mass. By making the solid content concentration of the solution containing the (meth) acrylic copolymer within the above range, the coating property of the applied adhesive is easily improved in the manufacture of the adhesive tape described later, and the adhesion of the obtained adhesive tape becomes more excellent. The more preferred lower limit of the solid content concentration of the solution containing the (meth) acrylic copolymer is 20% by mass, the further preferred lower limit is 30% by mass, the more preferred upper limit is 70% by mass, and the further preferred upper limit is 65% by mass.

[0130] In addition, in this specification, "solid content" refers to the component other than the solvent in the solution.

[0131] The preferred lower limit of the viscosity of the solution containing the (meth)acrylic acid copolymer at 23°C is 500 mPa·s, and the preferred upper limit is 12000 mPa·s. By setting the viscosity of the solution containing the (meth)acrylic acid copolymer at 23°C to be within this range, the adhesion of the obtained adhesive tape becomes more excellent. The more preferred lower limit of the viscosity of the solution containing the (meth)acrylic acid copolymer at 23°C is 1000 mPa·s, and the further preferred lower limit is 2000 mPa·s, and the more preferred upper limit is 10000 mPa·s, and the further preferred upper limit is 8000 mPa·s.

[0132] The viscosity of the solution containing the (meth)acrylic acid-based copolymer at 23° C. can be determined, for example, by the following method.

[0133] Specifically, 400 mL of a solution containing a (meth)acrylic acid-based copolymer is weighed into a 500 mL polypropylene cup and measured using a B-type viscometer at 23° C. and 10 rpm to determine the viscosity at 23° C.

[0134] As a method for adjusting the viscosity of the solution containing the (meth)acrylic acid copolymer at 23° C. to the above range, preferably, a method of adjusting the composition and weight average molecular weight of the (meth)acrylic acid copolymer, and the solid content concentration and solvent of the solution containing the (meth)acrylic acid copolymer is adopted.

[0135] The pressure-sensitive adhesive layer preferably further contains a silane coupling agent.

[0136] When the pressure-sensitive adhesive layer contains a silane coupling agent, the obtained pressure-sensitive adhesive tape has higher pressure-sensitive adhesive strength.

[0137] Examples of the silane coupling agent include vinyl trimethoxysilane, vinyl triethoxysilane, γ-methacryloxypropyl trimethoxysilane, γ-methacryloxypropyl methyl dimethoxysilane, γ-glycidoxypropyl trimethoxysilane, γ-glycidoxypropyl methyl dimethoxysilane, γ-glycidoxypropyl methyl diethoxysilane, γ-glycidoxypropyl triethoxysilane, 2-(3,4-epoxycyclohexane)- The following are preferred silanes: γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethylmethoxysilane, N-(2-aminoethyl)3-aminopropyltriethoxysilane, N-(2-aminoethyl)3-aminopropylmethyldimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, mercaptobutyltrimethoxysilane, γ-mercaptopropylmethyldimethoxysilane, etc. Among them, γ-glycidoxypropyltrimethoxysilane and γ-mercaptopropyltrimethoxysilane are preferred from the viewpoint of being easier to improve the adhesive strength of the obtained adhesive tape.

[0138] The preferred lower limit of the content of the silane coupling agent is 0.01 parts by mass, and the preferred upper limit is 5 parts by mass relative to 100 parts by mass of the (meth) acrylic copolymer. By making the silane coupling agent 0.01 parts by mass or more, the resulting adhesive tape has a higher adhesive force. By making the silane coupling agent 5 parts by mass or less, the oozing of the silane coupling agent at the bonding interface can be suppressed, and the resulting adhesive tape has a higher adhesive force. The more preferred lower limit of the content of the silane coupling agent is 0.1 parts by mass, the further preferred lower limit is 0.2 parts by mass, the more preferred upper limit is 1 part by mass, and the further preferred upper limit is 0.5 parts by mass.

[0139] The pressure-sensitive adhesive layer preferably further contains a cross-linking agent.

[0140] By making the pressure-sensitive adhesive layer contain a crosslinking agent, crosslinking of the pressure-sensitive adhesive layer is induced, so that the obtained pressure-sensitive adhesive tape has higher adhesive strength and further improves the adhesion to the adherend.

[0141] Examples of the crosslinking agent include isocyanate crosslinking agents, aziridine crosslinking agents, epoxy crosslinking agents, and metal chelate crosslinking agents. Among them, from the perspective of better adhesion of the adhesive tape to an adherend and better optical transparency even when exposed to a high temperature and high humidity environment, at least one crosslinking agent selected from the group consisting of isocyanate crosslinking agents, aziridine crosslinking agents, and epoxy crosslinking agents is preferred, and isocyanate crosslinking agents are more preferred.

[0142] The preferred lower limit of the content of the crosslinking agent is 0.01 parts by mass, and the preferred upper limit is 7 parts by mass, relative to 100 parts by mass of the (meth)acrylic copolymer. By setting the content of the crosslinking agent to be within this range, the shear storage modulus of the adhesive layer at 23° C. described later is more likely to satisfy an appropriate range, and the adhesive force of the obtained adhesive tape is further improved. The more preferred lower limit of the content of the crosslinking agent is 0.1 parts by mass, and the more preferred upper limit is 5 parts by mass.

[0143] In addition, the content of the said cross-linking agent shows the amount of the solid content of the said cross-linking agent.

[0144] The pressure-sensitive adhesive layer may further contain a cross-linking catalyst for accelerating cross-linking by the cross-linking agent.

[0145] Examples of the cross-linking catalyst include dibutyltin dilaurate, dibutyltin diacetate, and dioctyltin dilaurate, as cross-linking catalysts for the isocyanate-based cross-linking agents.

[0146] The lower limit of the content of the crosslinking catalyst is preferably 0.001 parts by mass, more preferably 0.01 parts by mass, and the upper limit is preferably 3 parts by mass, more preferably 1 part by mass, based on 100 parts by mass of the (meth)acrylic copolymer.

[0147] The pressure-sensitive adhesive layer may further contain a tackifier resin from the viewpoint of further improving the adhesive strength of the pressure-sensitive adhesive tape, but preferably contains no tackifier resin from the viewpoint of improving optical transparency.

[0148] The pressure-sensitive adhesive layer may contain additives such as a plasticizer, a softener, a filler, a pigment, and a dye as necessary.

[0149] The preferred lower limit of the gel fraction of the above-mentioned adhesive layer is 40% by mass, and the preferred upper limit is 95% by mass. By making the gel fraction of the above-mentioned adhesive layer more than 40% by mass, the durability of the above-mentioned adhesive layer for the offset and deformation of the adherend under the high temperature and high humidity environment is further improved, so that the adhesion of the obtained adhesive tape to the adherend is also further improved. By making the gel fraction of the above-mentioned adhesive layer less than 95% by mass, the above-mentioned adhesive layer will not become too hard, and the obtained adhesive tape has higher adhesive force. The more preferred lower limit of the gel fraction of the above-mentioned adhesive layer is 45% by mass, and the further preferred lower limit is 50% by mass, and the more preferred upper limit is 92.5% by mass, and the further preferred upper limit is 90% by mass.

[0150] In addition, the gel fraction of the said pressure-sensitive adhesive layer is measured by the following method.

[0151] That is, first, the adhesive tape having the above-mentioned adhesive layer is cut into a plane rectangle of 20 mm × 40 mm to prepare a test piece, and the test piece is immersed in ethyl acetate at 23°C for 24 hours, taken out from ethyl acetate, and dried at 110°C for 1 hour. The mass of the test piece after drying is measured, and the gel fraction is calculated using the following formula (I). It should be noted that the release film for protecting the above-mentioned adhesive layer is not laminated on the test piece. In addition, when the test piece does not have a substrate, W0=0 is set to calculate the gel fraction.

[0152] Gel fraction (mass %) = 100 × (W2-W0) / (W1-W0) (I)

[0153] (W0: mass of substrate, W1: mass of test piece before immersion, W2: mass of test piece after immersion and drying)

[0154] The preferred lower limit of the shear storage modulus of the adhesive layer at 23°C is 0.5×10 5 Pa, the upper limit of which is preferably 3.0×10 6 By setting the shear storage modulus of the adhesive layer at 23°C within this range, the obtained adhesive tape has a higher adhesive force and further improves the adhesion to the adherend. A more preferred lower limit of the shear storage modulus of the adhesive layer at 23°C is 0.7×10 5 Pa, and a further preferred lower limit is 0.9×10 5 Pa, and a further preferred lower limit is 1.0×10 5 Pa, the lower limit of which is particularly preferred is 2.0×10 5 Pa, and the more preferred upper limit is 2.0×10 6 Pa, and a further preferred upper limit is 1.0×10 6Pa, and a further preferred upper limit is 5.0×10 5 Pa.

[0155] The shear storage modulus of the pressure-sensitive adhesive layer at 23° C. can be determined, for example, by the following method.

[0156] That is, the adhesive constituting the adhesive layer is applied to the release-treated surface of the release-treated PET film in such a manner that the thickness of the adhesive layer after drying becomes 1000 μm and dried. Alternatively, the adhesive layer is formed by overlapping the adhesive layers so that the thickness becomes 1000 μm. For the obtained adhesive layer having a thickness of 100 μm, a dynamic viscoelasticity measuring device (e.g., "DVA-200" manufactured by IT Measurement and Control Co., Ltd.) is used to measure the dynamic viscoelasticity spectrum under the conditions of shear direction, frequency of 10 Hz, heating rate of 5°C / min, and temperature range of -50°C to 200°C, thereby determining the shear storage modulus at 23°C.

[0157] As a method for adjusting the gel fraction of the pressure-sensitive adhesive layer and the shear storage modulus of the pressure-sensitive adhesive layer at 23° C. to the above ranges, preferably, the composition and weight average molecular weight of the (meth)acrylic copolymer are adjusted, and when the cross-linking agent is used, the type and content thereof are adjusted.

[0158] The acid value of the adhesive layer is preferably 5 mgKOH / g or less. By setting the acid value of the adhesive layer to 5 mgKOH / g or less, the metal corrosiveness of the obtained adhesive tape can be further suppressed. The more preferred upper limit of the acid value of the adhesive layer is 1 mgKOH / g.

[0159] The lower limit of the acid value of the adhesive layer is not particularly limited, and may be 0 mgKOH / g.

[0160] The acid value of the pressure-sensitive adhesive layer can be measured by the same method as the acid value of the (meth)acrylic acid-based copolymer.

[0161] As a method for adjusting the acid value of the above-mentioned pressure-sensitive adhesive layer to fall within the above-mentioned range, the above-mentioned method of adjusting the composition and acid value of the above-mentioned (meth)acrylic acid-based copolymer is preferred.

[0162] The pressure-sensitive adhesive tape of the present invention may be an unsupported tape having no substrate or a supported tape having a substrate. From the viewpoint of making the pressure-sensitive adhesive tape of the present invention thinner and having better optical transparency, an unsupported tape having no substrate is preferred.

[0163] When the pressure-sensitive adhesive tape of the present invention is a support tape having a substrate, it may be a single-sided pressure-sensitive adhesive tape having the pressure-sensitive adhesive layer on one side of the substrate or a double-sided pressure-sensitive adhesive tape having the pressure-sensitive adhesive layer on both sides of the substrate.

[0164] The substrate is not particularly limited, and a conventionally known substrate may be used. However, in order to increase the biogenic carbon content in the entire pressure-sensitive adhesive tape, a biogenic substrate is preferably used.

[0165] Examples of the bio-derived substrate include films and nonwoven fabrics containing polyester (PES) such as polyethylene terephthalate (PET), polyethylene furandicarboxylate (PEF), polylactic acid (PLA), polytrimethylene terephthalate (PTT), polybutylene terephthalate (PBT), and polybutylene succinate (PBS) derived from plants. In addition, films and nonwoven fabrics containing polyethylene (PE), polypropylene (PP), polyurethane (PU), triacetylcellulose (TAC), cellulose, and polyamide (PA) derived from plants are also included.

[0166] From the viewpoint of substrate strength, the substrate is preferably a film made of PES or a film made of PA. From the viewpoint of heat resistance and oil resistance, a film made of PA is preferred.

[0167] Examples of the constituent material of the film containing PA include nylon 11, nylon 1010, nylon 610, nylon 510, nylon 410, etc., which are made of castor oil, and nylon 56, which is made of cellulose.

[0168] In addition, from the viewpoint of reducing the environmental load by reducing the use of new petroleum resources and suppressing the emission of carbon dioxide, a substrate using renewable resources can be used. As a resource recycling method, for example, the following method can be cited: recycling waste such as packaging containers, household appliances, automobiles, building materials, food, and waste generated in the manufacturing process, and the material taken out is used as a raw material again by cleaning, decontamination, or decomposition based on heating and fermentation. As a substrate using the above-mentioned renewable resources, for example, films and non-woven fabrics including PET, PBT, PE, PP, PA, etc., which use the material obtained by resinifying the recycled plastic as a raw material, can be cited. In addition, the recycled waste can be burned and used as heat energy related to the manufacture of the substrate and its raw materials, and the grease contained in the above-mentioned waste recycled can also be mixed into petroleum, and used for raw materials after fractionation and purification.

[0169] From the viewpoint of improving compression characteristics, the substrate may be a foam substrate.

[0170] The foam substrate is preferably a foam substrate comprising at least one selected from PE, PP and PU, and is more preferably a foam substrate comprising PE from the viewpoint of achieving a high balance between flexibility and strength. Examples of the constituent of the foam substrate comprising PE include PE made from sugar cane.

[0171] As a method for producing the above-mentioned foam substrate, for example, the following method is preferred: preparing a foamable resin composition comprising a PE resin and a foaming agent, wherein the PE resin comprises PE made from sugar cane as a raw material, foaming the foaming agent when the foamable resin composition is extruded into a sheet using an extruder, and cross-linking the obtained polyolefin foam as needed.

[0172] The preferred lower limit of the thickness of the foam substrate is 50 μm, and the preferred upper limit is 5000 μm. By making the thickness of the foam substrate within this range, high impact resistance can be exerted, and high flexibility can be closely attached to the shape of the adherend. The more preferred upper limit of the thickness of the foam substrate is 1000 μm, and the further preferred upper limit is 300 μm.

[0173] The pressure-sensitive adhesive tape of the present invention may include other layers in addition to the pressure-sensitive adhesive layer and the substrate as long as the effects of the present invention are not impaired.

[0174] The method for producing the pressure-sensitive adhesive tape of the present invention is not particularly limited, and the pressure-sensitive adhesive tape can be produced by a conventionally known production method. For example, in the case of a double-sided pressure-sensitive adhesive tape, the following method can be mentioned.

[0175] First, a solvent is added to a (meth)acrylic copolymer and, if necessary, a crosslinking agent, etc. to prepare a solution of an adhesive A, which is then applied to the surface of a substrate, and the solvent in the solution is completely dried and removed to form an adhesive layer A. Next, a release film is overlapped on the formed adhesive layer A in a state where its release-treated surface faces the adhesive layer A.

[0176] Next, another release film other than the release film is prepared, and a solution of the adhesive B prepared by the same method as above is applied to the release treatment surface of the release film, and the solvent in the solution is completely dried and removed, thereby preparing a laminated film having an adhesive layer B formed on the surface of the release film. The obtained laminated film is overlapped on the back of the substrate having the adhesive layer A formed thereon in a state where the adhesive layer B faces the back of the substrate, to prepare a laminated body. Then, by pressurizing the laminated body with a rubber roller or the like, a double-sided adhesive tape having adhesive layers on both sides of the substrate and the surfaces of the adhesive layers covered by release films can be obtained.

[0177] Alternatively, two groups of laminated films may be prepared in the same manner, and the laminated films may be overlapped on both sides of a substrate so that the adhesive layer of the laminated films faces the substrate to prepare a laminate, and the laminate may be pressurized using a rubber roller or the like, thereby obtaining a double-sided adhesive tape having adhesive layers on both sides of the substrate and the surfaces of the adhesive layers covered with release films.

[0178] For the adhesive tape of the present invention, the preferred lower limit of the total thickness of the adhesive tape (the total thickness of the adhesive layer, substrate and other layers) is 5 μm, and the preferred upper limit is 6000 μm. By making the total thickness of the adhesive tape within this range, the adhesive force becomes higher. The more preferred upper limit of the total thickness of the adhesive tape is 1200 μm, and the further preferred upper limit is 500 μm.

[0179] The adhesive tape of the present invention preferably has a haze value (turbidity value) at room temperature (20° C. or higher and 25° C. or lower) (hereinafter, sometimes also referred to as “initial haze value at room temperature”) of less than 3.0%. By making the haze value at room temperature less than 3.0%, the adhesive tape of the present invention can be suitably used for applications requiring optical transparency such as bonding of display panel modules.

[0180] In addition, the lower limit of the haze value at room temperature is not particularly limited, and the lower the haze value, the more preferred it is, and may be 0%.

[0181] The haze value at room temperature can be measured, for example, in accordance with JIS K 7136:2000 using a haze meter (for example, “NDH 400” manufactured by Nippon Denshoku Industries, Ltd.).

[0182] The adhesive tape of the present invention preferably has a haze value (turbidity value) of less than 3.0% at room temperature (20°C or more and 25°C or less) after being left standing for 500 hours in an environment of 65°C and 90% RH. By making the haze value at room temperature after being left standing for 500 hours in an environment of 65°C and 90% RH less than 3.0%, the adhesive tape of the present invention can be suitable for applications requiring optical transparency such as bonding of display panel modules. In addition, the lower limit of the haze value at room temperature after being left standing for 500 hours in an environment of 65°C and 90% RH is not particularly limited, and the lower the haze value, the more preferred it is, and it can be 0%.

[0183] The haze value at room temperature after being left to stand for 500 hours under an environment of 65° C. and 90% RH is measured by the following method.

[0184] That is, first, two glass plates with a thickness of 0.7 mm and a width of 50 mm × a length of 80 mm are used, and the glass plates are bonded to both sides of the adhesive tape cut to the same size as the glass plates to prepare a test piece. It should be noted that no release film for protecting the above-mentioned adhesive layer is laminated on the test piece. Next, the obtained test piece is stored in an environment of 65°C and 90% RH for 500 hours, and then the temperature of the test piece is restored to room temperature (above 20°C and below 25°C) in an environment of 23°C and 50% RH. Then, after 1 hour, according to JIS K 7136:2000, a haze meter (for example, Nippon Denshoku Industries, "NDH 400") is used to measure the haze value of visible light at room temperature (above 20°C and below 25°C).

[0185] The preferred lower limit of the 180° peel strength of the adhesive tape of the present invention to glass at 23°C is 10 N / 25 mm, and the more preferred lower limit is 15 N / 25 mm. In addition, there is no particular upper limit to the 180° peel strength to glass at 23°C, and the higher the value, the better, but the actual upper limit is 50 N / 25 mm.

[0186] The 180° peel strength to glass at 23° C. is measured by the following method.

[0187] That is, first, the adhesive tape was cut into a width of 25 mm × a length of 75 mm to prepare a test piece. After the test piece was placed on the glass plate in a state where its adhesive layer was facing the glass plate, it was bonded to the test piece by reciprocating a 2 kg rubber roller once at a speed of 300 mm / min. Then, it was aged at 23°C and 50% RH for 20 minutes to prepare a test sample. Under the conditions of 23°C and 50% RH, the test sample was peeled off in the 180° direction at a tensile speed of 300 mm / min, and the adhesive force (N / 25mm) was measured.

[0188] It should be noted that, in the case where the adhesive tape is an unsupported tape having no substrate or a double-sided adhesive tape having adhesive layers on both sides of the substrate, a polyethylene terephthalate film with a thickness of 23 μm (for example, "FE2002" manufactured by FUTAMURA CHEMICAL Co., Ltd.) is placed on the surface of the adhesive layer on the other side (the side not to be measured) and then bonded to the glass plate.

[0189] The use of the adhesive tape of the present invention is not particularly limited, and is preferably used for fixing electronic components or vehicle-mounted components. Specifically, the adhesive tape of the present invention can be suitably used for bonding and fixing electronic components in large portable electronic devices, bonding and fixing vehicle-mounted components (such as vehicle-mounted panels), etc.

[0190] Effects of the Invention

[0191] According to the present invention, it is possible to provide a pressure-sensitive adhesive tape that can reduce environmental load and has excellent optical transparency even when exposed to a high-temperature and high-humidity environment. DETAILED DESCRIPTION

[0192] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.

[0193] <n-Heptyl acrylate containing biogenic carbon>

[0194] Ricinoleic acid derived from castor oil is cracked to obtain a mixture containing undecylenic acid and heptanol. Next, it is separated from undecylenic acid by distillation to obtain n-heptanol containing carbon from biological sources. n-heptyl acrylate is prepared by esterifying n-heptanol containing carbon from biological sources with acrylic acid (manufactured by Nippon Shokubai Co., Ltd.).

[0195] <2-Octyl acrylate containing biogenic carbon>

[0196] The ricinoleic acid derived from castor oil was subjected to alkali fusion to obtain a mixture containing sebacic acid and 2-octanol. Subsequently, the mixture was separated from the sebacic acid by distillation to obtain 2-octanol containing carbon derived from biological sources. 2-octyl acrylate was prepared by esterifying 2-octanol containing carbon derived from biological sources with acrylic acid (manufactured by Nippon Shokubai Co., Ltd.).

[0197] <Lauryl acrylate containing bio-derived carbon>

[0198] Lauric acid derived from coconut oil was subjected to catalytic reduction to obtain lauryl alcohol containing bio-derived carbon. Lauryl acrylate was prepared by esterifying lauryl alcohol containing bio-derived carbon with acrylic acid (manufactured by Nippon Shokubai Co., Ltd.).

[0199] <Isobornyl acrylate containing biogenic carbon>

[0200] Camphene containing bio-derived carbon was obtained by isomerizing pinene collected from rosin, and isobornyl acrylate containing bio-derived carbon was prepared by reacting camphene containing bio-derived carbon with acrylic acid (manufactured by Nippon Shokubai Co., Ltd.).

[0201] <Isobornyl methacrylate containing biogenic carbon>

[0202] Camphene containing bio-derived carbon is obtained by isomerizing pinene collected from rosin, and isobornyl methacrylate containing bio-derived carbon is prepared by reacting camphene containing bio-derived carbon with methacrylic acid (manufactured by Mitsubishi Chemical Co., Ltd.).

[0203] <Other monomers (not containing biogenic carbon)>

[0204] ·Methyl methacrylate (Mitsubishi Chemical Co., Ltd.)

[0205] · n-Butyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0206] ·2-Ethylhexyl acrylate (Mitsubishi Chemical Co., Ltd.)

[0207] ·2-Hydroxyethyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd.)

[0208] ·4-Hydroxybutyl acrylate (manufactured by Nippon Shokubai Co., Ltd.)

[0209] ·2-Hydroxypropyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0210] ・Acrylonitrile (Mitsubishi Chemical Co., Ltd.)

[0211] ・Acrylamide (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0212] ·Dimethylacrylamide (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0213] ·Acrylic acid (manufactured by Nippon Shokubai Co., Ltd.)

[0214] <Cross-linking agent>

[0215] ・Isocyanate crosslinking agent (manufactured by Tosoh Corporation, "CORONATE HX")

[0216] <Silane coupling agent>

[0217] Silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., "KBM-403")

[0218] (Example 1)

[0219] (1) Production of (meth)acrylic acid copolymer

[0220] Ethyl acetate as a polymerization solvent was added to the reaction container, and after bubbling with nitrogen, the reaction container was heated while nitrogen was flowing in to start reflux. Next, a polymerization initiator solution obtained by diluting 0.1 parts by mass of azobisisobutyronitrile as a polymerization initiator by 10 times with ethyl acetate was put into the reaction container, and 39.95 parts by mass of n-heptyl acrylate containing carbon from biological sources, 40 parts by mass of n-butyl acrylate, 20 parts by mass of 2-hydroxyethyl acrylate, and 0.05 parts by mass of acrylic acid were added dropwise over 2 hours. After the dropwise addition was completed, a polymerization initiator solution obtained by diluting 0.1 parts by mass of azobisisobutyronitrile as a polymerization initiator by 10 times with ethyl acetate was again put into the reaction container, and a polymerization reaction was carried out for 4 hours to obtain a solution containing a (meth)acrylic acid copolymer.

[0221] In addition, the obtained (meth)acrylic acid copolymer was diluted 50 times with tetrahydrofuran (THF), and the obtained dilution was filtered with a filter (material: polytetrafluoroethylene, pore size: 0.2 μm) to prepare a measurement sample. The measurement sample was supplied to a gel permeation chromatograph (manufactured by Waters, "2690 Separations Module"), and GPC measurement was performed under the conditions of a sample flow rate of 1 mL / min and a column temperature of 40°C to measure the polystyrene-equivalent molecular weight of the acrylic acid copolymer and obtain the weight average molecular weight. The results are shown in Table 1.

[0222] (2) Viscosity of a solution containing a (meth)acrylic acid copolymer at 23°C

[0223] 400 mL of the obtained (meth)acrylic acid copolymer-containing solution was weighed into a 500 mL polypropylene cup, and the viscosity at 23° C. was measured using a B-type viscometer (manufactured by Tokyo Keiki Co., Ltd.) at 23° C. and 10 rpm. The results are shown in Table 1.

[0224] (3) Manufacturing of adhesive tape

[0225] In the obtained solution containing a (meth)acrylic acid copolymer, 0.2 parts by weight of a solid content of an isocyanate crosslinking agent (manufactured by Tosoh Corporation, "CORONATE HX") and 0.3 parts by weight of a silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., "KBM-403") were added to 100 parts by weight of the (meth)acrylic acid copolymer to prepare an adhesive. The adhesive was applied to a release-treated surface of a release PET film having a thickness of 75 μm so that the thickness of the adhesive layer after drying was 100 μm, and then dried at 110° C. for 5 minutes. The obtained adhesive layer was overlapped on the release-treated surface of a release PET film having a thickness of 75 μm, and aged at 40° C. for 48 hours to obtain an adhesive tape (unsupported type).

[0226] (4) Biogenic carbon content in adhesive layer

[0227] The biogenic carbon content of the obtained adhesive layer was measured in accordance with ASTM D6866-22. The results are shown in Table 1.

[0228] (5) Gel fraction of adhesive layer

[0229] The release PET film on one side of the obtained adhesive tape was peeled off, and it was attached to a PET film with a thickness of 23 μm (manufactured by FUTAMURA CHEMICAL, "FE2002"), and cut into a flat rectangle of 20 mm × 40 mm. In addition, the release PET film on the other side of the adhesive tape was peeled off to prepare a test piece, and the mass was measured. After the test piece was immersed in ethyl acetate at 23°C for 24 hours, it was taken out from ethyl acetate and dried at 110°C for 1 hour. The mass of the dried test piece was measured, and the gel fraction was calculated using the following formula (I). The results are shown in Table 1.

[0230] Gel fraction (mass %) = 100 × (W2-W0) / (W1-W0) (I)

[0231] (W0: mass of substrate (PET film), W1: mass of test piece before immersion, W2: mass of test piece after immersion and drying)

[0232] (6) Shear storage modulus of adhesive layer at 23°C

[0233] The obtained adhesive layer was overlapped so as to have a thickness of 1000 μm to prepare a measurement sample. The dynamic viscoelasticity spectrum of the measurement sample was measured under the conditions of shear direction, frequency of 10 Hz, heating rate of 5°C / min, and temperature range of -50°C to 200°C using a dynamic viscoelasticity measuring device (manufactured by IT Measurement and Control Co., Ltd., "DVA-200"). Thus, the shear storage modulus at 23°C was obtained. The results are shown in Table 1.

[0234] (7) Water vapor transmission coefficient P of the adhesive layer

[0235] The obtained adhesive layer was cut into pieces of about 10 cm × 10 cm and placed in the measuring section of a water vapor transmission rate measuring device (manufactured by MOCON, “PERMATRAN-W 1 / 50”). The water vapor transmission rate WVTR (g / (m2) of the adhesive layer at 40°C and 90%RH was measured by a moisture transmission test based on the MOCON method in accordance with JIS K 7129B under the conditions of 40°C and 90%RH. 2 ·day)).

[0236] The water vapor permeability coefficient P (g·mm / (m 2 The results are shown in Table 1.

[0237] (Examples 2 to 40, 47 to 49, Comparative Examples 1 to 4)

[0238] A pressure-sensitive adhesive tape was obtained in the same manner as in Example 1 except that the type and blending amount of the monomer constituting the (meth)acrylic acid copolymer were changed as shown in Tables 1 to 6. In addition, in the same manner as in Example 1, the weight average molecular weight of the (meth)acrylic acid copolymer, the viscosity of the solution containing the (meth)acrylic acid copolymer at 23°C, the content of biogenic carbon in the pressure-sensitive adhesive layer, the gel fraction of the pressure-sensitive adhesive layer, the shear storage modulus of the pressure-sensitive adhesive layer at 23°C, and the water vapor permeability coefficient P of the pressure-sensitive adhesive layer were measured. The results are shown in Tables 1 to 6.

[0239] (Example 40)

[0240] The type and amount of monomers constituting the (meth)acrylic acid copolymer were changed as shown in Table 5, and a polymerization initiator solution obtained by diluting 0.8 parts by mass of t-butyl peroxy-2-ethylhexanoate (manufactured by NOF Corporation, "PERBUTYL O") and t-hexyl peroxypivalate (manufactured by NOF Corporation, "PERBUTYLPV") by 10 times with ethyl acetate was added to the reaction container instead of azobisisobutyronitrile as a polymerization initiator to obtain a solution containing a (meth)acrylic acid copolymer. A pressure-sensitive adhesive tape was obtained in the same manner as in Example 1. In addition, in the same manner as in Example 1, the weight average molecular weight of the (meth)acrylic acid copolymer, the viscosity of the solution containing the (meth)acrylic acid copolymer at 23°C, the content of biogenic carbon in the pressure-sensitive adhesive layer, the gel fraction of the pressure-sensitive adhesive layer, the shear storage modulus of the pressure-sensitive adhesive layer at 23°C, and the water vapor transmission coefficient P of the pressure-sensitive adhesive layer were measured. The results are shown in Table 5.

[0241] (Example 41)

[0242] The type and amount of monomers constituting the (meth)acrylic acid-based copolymer were changed as shown in Table 5, and a pressure-sensitive adhesive tape was obtained in the same manner as in Example 1 except that azobisisobutyronitrile was not used as a polymerization initiator and a polymerization initiator solution prepared by diluting 1,1-di(tert-hexylperoxy)cyclohexane (manufactured by NOF Corporation, “PERHEXA HC”), 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate (manufactured by NOF Corporation, “PEROCTA O”) and tert-hexyl peroxypivalate (manufactured by NOF Corporation, “PERHEXYL PV”) by 10 times with ethyl acetate was added to the reaction vessel to obtain a solution containing a (meth)acrylic acid-based copolymer. In addition, the weight average molecular weight of the (meth)acrylic acid copolymer, the viscosity of the solution containing the (meth)acrylic acid copolymer at 23°C, the content of biogenic carbon in the adhesive layer, the shear storage modulus of the adhesive layer at 23°C, and the water vapor permeability coefficient P of the adhesive layer were measured in the same manner as in Example 1. The results are shown in Table 5.

[0243] (Example 42)

[0244] The type and amount of monomers constituting the (meth)acrylic acid copolymer were changed as shown in Table 5, and a polymerization initiator solution prepared by diluting 1,1-di(tert-hexylperoxy)cyclohexane (manufactured by NOF Corporation, “PERHEXA HC”), tert-butyl peroxy-2-ethylhexanoate (manufactured by NOF Corporation, “PERBUTYL O”), and tert-butyl peroxypivalate (manufactured by NOF Corporation, “PERBUTYL PV”) by 10 times with ethyl acetate was added to the reaction vessel instead of azobisisobutyronitrile to obtain a solution containing the (meth)acrylic acid copolymer. A pressure-sensitive adhesive tape was obtained in the same manner as in Example 1. In addition, the weight average molecular weight of the (meth)acrylic acid copolymer, the viscosity of the solution containing the (meth)acrylic acid copolymer at 23° C., the content of biogenic carbon in the pressure-sensitive adhesive layer, the gel fraction of the pressure-sensitive adhesive layer, the shear storage modulus of the pressure-sensitive adhesive layer at 23° C., and the water vapor permeability coefficient P of the pressure-sensitive adhesive layer were measured in the same manner as in Example 1. The results are shown in Table 5.

[0245] (Example 43)

[0246] The type and amount of monomers constituting the (meth)acrylic acid copolymer were changed as shown in Table 5, and as a polymerization initiator, a polymerization initiator solution prepared by diluting 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate (manufactured by NOF Corporation, "PEROCTA O") and tert-hexyl peroxypivalate (manufactured by NOF Corporation, "PERHEXYL PV") by 10 times with ethyl acetate was added to the reaction container instead of azobisisobutyronitrile to obtain a solution containing the acrylic acid copolymer. A pressure-sensitive adhesive tape was obtained in the same manner as in Example 1. In addition, in the same manner as in Example 1, the weight average molecular weight of the (meth)acrylic acid copolymer, the viscosity of the solution containing the (meth)acrylic acid copolymer at 23°C, the content of biogenic carbon in the pressure-sensitive adhesive layer, the gel fraction of the pressure-sensitive adhesive layer, the shear storage modulus of the pressure-sensitive adhesive layer at 23°C, and the water vapor permeability coefficient P of the pressure-sensitive adhesive layer were measured. The results are shown in Table 5.

[0247] (Example 44)

[0248] As shown in Table 5, the type and amount of monomers constituting the (meth)acrylic acid copolymer were changed, and as a polymerization initiator, a polymerization initiator solution prepared by diluting 1,1-di(tert-hexylperoxy)cyclohexane (manufactured by NOF Corporation, "PERHEXA HC") and tert-hexyl peroxypivalate (manufactured by NOF Corporation, "PERHEXYLPV") by 10 times with ethyl acetate was added to the reaction container instead of azobisisobutyronitrile to obtain a solution containing the acrylic acid copolymer. A pressure-sensitive adhesive tape was obtained in the same manner as in Example 1. In addition, in the same manner as in Example 1, the weight average molecular weight of the (meth)acrylic acid copolymer, the viscosity of the solution containing the (meth)acrylic acid copolymer at 23°C, the content of biogenic carbon in the pressure-sensitive adhesive layer, the gel fraction of the pressure-sensitive adhesive layer, the shear storage modulus of the pressure-sensitive adhesive layer at 23°C, and the water vapor transmission coefficient P of the pressure-sensitive adhesive layer were measured. The results are shown in Table 5.

[0249] (Example 45)

[0250] The type and amount of monomers constituting the (meth)acrylic acid copolymer were changed as shown in Table 5, and as a polymerization initiator, a polymerization initiator solution of 0.6 parts by mass of tert-butyl peroxy-2-ethylhexanoate (manufactured by NOF Corporation, "PERBUTYL O") and tert-hexyl peroxypivalate (manufactured by NOF Corporation, "PERHEXYLPV") diluted 10 times with ethyl acetate was added to the reaction container instead of azobisisobutyronitrile to obtain a solution containing the acrylic acid copolymer. The same operation as in Example 1 was performed to obtain an adhesive tape. In addition, the weight average molecular weight of the (meth)acrylic acid copolymer, the viscosity of the solution containing the (meth)acrylic acid copolymer at 23°C, the content of biogenic carbon in the adhesive layer, the gel fraction of the adhesive layer, the shear storage modulus of the adhesive layer at 23°C, and the water vapor transmission coefficient P of the adhesive layer were measured in the same manner as in Example 1. The results are shown in Table 5.

[0251] (Example 46)

[0252] The type and amount of monomers constituting the (meth)acrylic acid-based copolymer were changed as shown in Table 5, and a pressure-sensitive adhesive tape was obtained in the same manner as in Example 1 except that azobisisobutyronitrile was not used as a polymerization initiator and a polymerization initiator solution prepared by diluting 1,1-di(tert-hexylperoxy)cyclohexane (manufactured by NOF Corporation, “PERHEXA HC”), 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate (manufactured by NOF Corporation, “PEROCTA O”) and tert-butyl peroxypivalate (manufactured by NOF Corporation, “PERBUTYL PV”) by 10 times with ethyl acetate was added to the reaction vessel to obtain a solution containing a (meth)acrylic acid-based copolymer. In addition, the weight average molecular weight of the (meth)acrylic acid copolymer, the viscosity of the solution containing the (meth)acrylic acid copolymer at 23°C, the content of biogenic carbon in the adhesive layer, the gel fraction of the adhesive layer, the shear storage modulus of the adhesive layer at 23°C, and the water vapor permeability coefficient P of the adhesive layer were measured in the same manner as in Example 1. The results are shown in Table 5.

[0253] <Evaluation>

[0254] The pressure-sensitive adhesive tapes obtained in Examples and Comparative Examples were evaluated by the following methods. The results are shown in Tables 1 to 6.

[0255] (Environmental load reduction)

[0256] The environmental load reduction performance of the adhesive tape was evaluated by the method shown in the above-mentioned “(4) Content of biogenic carbon in the adhesive layer”, with the content of biogenic carbon in the adhesive layer being 60% or more being marked as “◎”, the content being 50% or more and less than 60% being marked as “○”, the content being 30% or more and less than 50% being marked as “△”, and the content being less than 30% being marked as “×”.

[0257] (Optical transparency)

[0258] (1) Initial haze value at room temperature

[0259] The obtained adhesive tape was cut into a width of 50 mm × a length of 80 mm, and one release PET film was peeled off and attached to a glass plate of 0.7 mm thickness, 50 mm width × 80 mm length. Next, the other release PET film of the adhesive tape was peeled off and attached to another glass plate of 0.7 mm thickness, 50 mm width × 80 mm length to prepare a test piece. Immediately after the test piece was prepared, the haze value of visible light at the initial room temperature was measured using a haze meter (manufactured by Nippon Denshoku Industries, "NDH 400").

[0260] The optical transparency of the pressure-sensitive adhesive tape was evaluated by evaluating the haze value of less than 1.0%, 1.0% or more and less than 3.0% as "○", and 3.0% or more as "×".

[0261] (2) Haze value at room temperature after standing for 500 hours in an environment of 65°C and 90% RH

[0262] The obtained adhesive tape was cut into a width of 50 mm × a length of 80 mm, and one release PET film was peeled off and attached to a glass plate of 0.7 mm thickness, 50 mm width × 80 mm length. Next, the other release PET film of the adhesive tape was peeled off and attached to another glass plate of 0.7 mm thickness, 50 mm width × 80 mm length to prepare a test piece. After the obtained test piece was left to stand for 500 hours in an environment of 65°C and 90% RH, the temperature of the test piece was returned to room temperature (20°C or more and 25°C or less) in an environment of 23°C and 50% RH, and then one hour later, the haze value of visible light at room temperature was measured using a haze meter (manufactured by Nippon Denshoku Industries, "NDH 400") in accordance with JIS K 7136:2000.

[0263] The optical transparency of the pressure-sensitive adhesive tape was evaluated by evaluating the haze value of less than 1.0%, 1.0% or more and less than 3.0% as "○", and 3.0% or more as "×".

[0264] (Adhesion: 180° peel strength to glass at 23°C)

[0265] One release PET film of the obtained adhesive tape was peeled off, and after padding with a PET film of 23 μm thickness (manufactured by FUTAMURACHEMICAL, "FE2002"), it was cut into a width of 25 mm × a length of 75 mm, and the other release PET film was peeled off to prepare a test piece. After the test piece was placed on the glass plate in a state where the adhesive layer (the side to be measured) was facing the glass plate, it was bonded by reciprocating a 2 kg rubber roller on the test piece once at a speed of 300 mm / min. Then, it was aged at 23°C and 50% RH for 20 minutes to prepare a test sample. For the obtained test sample, it was peeled in the 180° direction under the conditions of 23°C, 50% RH, and a tensile speed of 300 mm / min, and the 180° peeling force (N / 25mm) was measured.

[0266] The 180° peeling strength to glass at 23°C was evaluated by indicating a value of 12 N / mm or more, 8 N / mm or more and less than 12 N / mm, and △ or less than 8 N / mm.

[0267] (Appearance when attached to glass)

[0268] The obtained adhesive tape was cut into a width of 50 mm × a length of 80 mm, and one release PET film was peeled off and attached to a glass plate of 0.7 mm thickness, 50 mm width × 80 mm length. Next, the other release PET film of the adhesive tape was peeled off and attached to another glass plate of 0.7 mm thickness, 50 mm width × 80 mm length to prepare a test sample. For the obtained test sample, a digital microscope (manufactured by KEYENCE, product name VHX-900) was used to observe the interface between the glass plate and the adhesive layer of the adhesive tape. The case where no bubbles with a diameter of 0.5 mm or more were observed between the glass plate and the adhesive layer was recorded as "○", and the case where bubbles with a diameter of 0.5 mm or more were observed was recorded as "×".

[0269] (Metal corrosion: corrosion of copper foil)

[0270] One release PET film of the obtained adhesive tape was peeled off, and the adhesive layer was bonded to a 50 μm thick PET film (E5200 manufactured by Toyobo Co., Ltd.), and cut into 25 mm wide x 25 mm long to prepare an adhesive tape for evaluation. Two adhesive tapes for evaluation were prepared.

[0271] Another release PET film was peeled off from the evaluation adhesive tape 1, and the adhesive layer was placed in a state facing one side of the copper foil (manufactured by Takeuchi Metal Foil Powder Industry Co., Ltd., "C1020R-H", thickness 20μm, width 25mm×length 25mm), and then laminated by reciprocating a 2kg rubber roller once at a speed of 300mm / min on the evaluation adhesive tape 1. Then, another release PET film was peeled off from the evaluation adhesive tape 2, and the adhesive layer was placed in a state facing the other side of the copper foil, and then laminated by reciprocating a 2kg rubber roller once at a speed of 300mm / min on the evaluation adhesive tape 2, to produce a laminate of width 25mm×length 25mm. After lamination, the laminate was aged for 20 minutes under the conditions of 23°C and 50%RH to produce a test sample.

[0272] The test sample was placed in an environment of 85°C and 85% RH. After 3 days, the evaluation adhesive tape 1 and the evaluation adhesive tape 2 were peeled off from the copper foil and the corrosion of the copper foil was visually checked. The case where no corrosion of the copper foil was observed on both sides of the copper foil was recorded as "○", and the case where corrosion was observed on at least one side of the copper foil was recorded as "×". The corrosion of the copper foil was determined and the metal corrosion of the adhesive tape was evaluated.

[0273] Even if the corrosion of the copper foil was judged as "×", the adhesive tape of the present invention can be used without any problem depending on the application.

[0274]

[0275]

[0276]

[0277]

[0278]

[0279]

[0280] Industrial Applicability

[0281] According to the present invention, it is possible to provide a pressure-sensitive adhesive tape that can reduce environmental load and has excellent optical transparency even when exposed to a high-temperature and high-humidity environment.

Claims

1. An adhesive tape, characterized in that: having an adhesive layer, The adhesive layer contains a (meth)acrylic acid copolymer, The content of biogenic carbon in the adhesive layer is 30% or more, The adhesive tape satisfies at least one configuration selected from the following first configuration and the following second configuration, The first configuration is as follows: the water vapor permeability coefficient P of the adhesive layer calculated by the following formula (i) is 11 g·mm / (m 2 ·day) or above, In formula (i), WVTR represents the water vapor transmission rate per unit area of ​​the adhesive layer under an environment of 40° C. and 90% RH for one day, and t represents the thickness of the adhesive layer. The unit of the water vapor transmission rate is g / (m 2 ·day), the unit of thickness is mm; Second configuration: The (meth)acrylic copolymer includes at least one structural unit selected from the group consisting of a structural unit derived from n-heptyl (meth)acrylate and a structural unit derived from 2-octyl (meth)acrylate, and a structural unit derived from a nitrogen atom-containing monomer. 2 . The pressure-sensitive adhesive tape according to claim 1 , satisfying the first configuration.

3. The adhesive tape according to claim 2, wherein The (meth)acrylic copolymer includes at least one structural unit selected from the group consisting of a structural unit derived from n-heptyl (meth)acrylate and a structural unit derived from 2-octyl (meth)acrylate.

4. The adhesive tape according to claim 2 or 3, wherein The (meth)acrylic copolymer includes at least one structural unit selected from the group consisting of a structural unit derived from a hydroxyl group-containing monomer and a structural unit derived from a nitrogen atom-containing monomer. 5 . The pressure-sensitive adhesive tape according to claim 1 , 2 , 3 or 4 , which satisfies the second configuration.

6. The adhesive tape according to claim 5, wherein The (meth)acrylic copolymer further includes a structural unit derived from a hydroxyl group-containing monomer.

7. The adhesive tape according to claim 4 or 6, wherein The content ratio of the structural unit derived from the hydroxyl group-containing monomer in the (meth)acrylic copolymer is 5% by mass or more and 30% by mass or less.

8. The adhesive tape according to claim 1, 2, 3, 4, 5, 6 or 7, wherein: The (meth)acrylic copolymer includes a structural unit derived from a (meth)acrylic acid ester including bio-derived carbon.

9. The adhesive tape according to claim 8, wherein At least one structural unit selected from the structural unit derived from n-heptyl(meth)acrylate and the structural unit derived from 2-octyl(meth)acrylate contains biogenic carbon.

10. The adhesive tape according to claim 4, 5, 6, 7, 8 or 9, wherein: The structural unit derived from the nitrogen atom-containing monomer includes a structural unit derived from an amide group-containing monomer.

11. The adhesive tape according to claim 4, 5, 6, 7, 8, 9 or 10, wherein The content ratio of the structural unit derived from the nitrogen atom-containing monomer in the (meth)acrylic copolymer is 5% by mass or more and 10% by mass or less.

12. The adhesive tape according to claim 4, 5, 6, 7, 8, 9, 10 or 11, wherein The total content ratio of the structural unit derived from the hydroxyl group-containing monomer and the structural unit derived from the nitrogen atom-containing monomer in the (meth)acrylic copolymer is 10% by mass or more and 30% by mass or less.

13. The adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12, wherein The (meth)acrylic acid-based copolymer includes a structural unit derived from a carboxyl group-containing monomer, and a content ratio of the structural unit derived from the carboxyl group-containing monomer in the (meth)acrylic acid-based copolymer is less than 0.5% by mass.

14. The adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 or 13, wherein The (meth)acrylic copolymer includes a structural unit derived from isobornyl (meth)acrylate.

15. The adhesive tape according to claim 14, wherein The content ratio of the structural unit derived from isobornyl (meth)acrylate in the (meth)acrylic acid-based copolymer is 10% by mass or more and 45% by mass or less.

16. The adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15, wherein The (meth)acrylic copolymer has a weight average molecular weight Mw of 300,000 or more and 900,000 or less.

17. The adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 or 16, wherein The adhesive layer contains a silane coupling agent.

18. The adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16 or 17, wherein The pressure-sensitive adhesive layer has a gel fraction of 40% by mass or more and 95% by mass or less.

19. The adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17 or 18, wherein The shear storage modulus of the adhesive layer at 23°C is 0.5×10 5 Pa or more and 3.0×10 6 Below Pa.

20. The adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 or 19, wherein the adhesive tape has a haze value of less than 3.0% at a temperature of 20°C or more and 25°C or less. The pressure-sensitive adhesive tape has a haze value of less than 3.0% at 20° C. or higher and 25° C. or lower after being left to stand for 500 hours under an environment of 65° C. and 90% RH.

21. The adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20, which has a 180° peel strength to glass of 10 N / 25 mm or more at 23°C.

Citation Information

Patent Citations

  • Thermally conductive adhesive tape, article and image display device

    JP2015021067A

  • Base material for heat-resistant adhesive tape and heat-resistant adhesive tape composed of the same

    JP2015052050A

  • Double-sided adhesive sheet

    JP2015120876A